The Importance of Chin Position on Perceived Attractiveness in Orthodontic Patient and Lay Person - Sadia Shabbir, Zain Rauf, Hana Pervez, Hijab Fatemah, Anam Sattar, Taskeen Khan (Pakistan Journal of Medical & Health Sciences, 2022)
Objectives: This study was conducted to determine the perceived attractiveness of the face by change in chin position between orthodontic patients and the general public and determine their desire for surgery to correct it. Study Design: Cross Sectional Study Setting: Orthodontic OPD, Period: March 2021- July 2021 Material & Methods: An ideal facial outline was created with a computer software. 150 participants, divided into two groups (pre-treatment orthodontic patients and lay person) were part of the research. Each participant was given a survey and asked to fill it out and rank images on a summative scale Results: Results showed that the aesthetic judgement of both observer groups was the same for most images; The rating was decided by the amount of shift in the chin position, with the scoring being higher when the chin was more forward than when it was backward. Keywords: attractiveness, chin position, esthetics, facial profile, orthodontics